Pengaruh Tax Avoidance, Ukuran Perusahaan, dan Dewan Komisaris Independen terhadap Kebijakan Transfer Pricing - Fatimah Sa'diah; Mayar Afriyenti (Universitas Negeri Padang, 2021)
The purpose of this research is to examine the effect of tax avoidance, size of company and independent board of commissioners in the companies that implement policy of transfer pricing. The population of this research are companies engaged in agriculture sector, mining sector and basic and chemical industrial sectors listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period which total 152 companies. The sampling method was carried out by purposive sampling method, so 85 companies were obtained as research samples. The analytical method used logistic regression analysis. The results of this research indicate that 1) tax avoidance does not effect on transfer pricing 2) the size of company has a positive effect on transfer pricing 3) independent commissioners does not effect on transfer pricing. The contribution of the independent variable in explaining the dependent variable in the amount of 11,5%, while the remaining 88,5% explained by other variables outside the model.